“Representations of Cognitive Metaphor in the Poem ‘The Ecstasies of the Third Night’ by the poet Ayach Yahiaoui.” - Amari, Ezzedine; Marhoun, Asia (El Omda in Linguistics and Discourse Analysis, 2021)
Secular linguistics has the great merit in establishing a new vision of the various ancient rhetorical concepts, especially with regard to the science of rhetoric, and especially with regard to metaphor. These have occupied a prominent place in rhetorical and literary studies, in the past and present, based on what has been said about their truth in that they are merely a verbal decoration adding to the meaning or an integral part of it, and what was said in its types and in its purpose in speech, up to what the interactive theory of borrowing adopted Which starts with an understanding of a metaphor from the way of thinking and understanding the world. Hence, this work seeks to shed light on the reality of "borrowing" and its types, in light of customary linguistics and an approach to all of this in the poem "The Steps of the Third Night"by the late Ayyash Yahyaoui.